The knowledge and Attitude Toward Orthodontic Treatment and its Perceived Oral-Health Effects among University Students in Derna City, Libya - Ranya Rafa Algadhy; Eman A. B. AGUORI; Ashraf Saad Elzer (المجلة الأفروآسيوية للبحث العلمي, 2025)
This study assesses the knowledge and attitudes of students at the University of Derna in Libya, regarding orthodontic treatment. A cross-sectional survey was conducted among 461 participants (34.3% males and 65.7% females) from both public and private universities. The questionnaire evaluated demographic data, awareness of orthodontic treatment, and attitudes toward orthodontic care. Overall, students demonstrated a high level of awareness, with most recognizing the role of orthodontists in correcting irregular teeth and understanding the aesthetic and functional importance of alignment. However, gaps were noted concerning the hereditary and habitual causes of malocclusion, such as tongue thrusting and mouth breathing. Female and science-major students showed slightly higher knowledge scores, though these differences were not statistically significant. Despite positive attitudes toward treatment, actual treatment uptake and adherence to post-treatment care remained low. The findings highlight the need for enhanced educational programs focusing on preventive and etiological aspects of orthodontic health among university students.